IMPORTANT RESEARCH ON THE MAINTENANCE OF SPEECH AND HUMAN HEALTH - Qodirqul Rozmatzoda; Nematjon Mamadaliev (American Journals Publishing, 2023)
The article discusses the place and role of the word as an important means of preserving human health in the scientific conclusions of natural scientists of foreign countries, summarizing the results achieved, the effective and appropriate use of the word, revealing the scientific, theoretical and methodological significance of the teaching manual dedicated to solving the actual scientific and philosophical problems of linguistics.
Keywords: linguistics, philosophy of language, sociology of language, speech art, sociolinguistics, lexicology, civilization, proprietor, spiritual factor, national language, national value, national identity, national idea.